Involutional entropion repair combining the modified Bick quick strip procedure with Quickert rotational sutures. (4th March 2019) - Golan, Shani; J. Lelli, Gary
ABSTRACT: Purpose : The purpose of the study was to determine the results of involutional entropion repair by combining the modified Bick strip procedure with Quickert rotational sutures. Methods : A retrospective review of consecutive patients with involutional entropion who underwent repair by combined Bick and Quickert technique from January 2013 to December 2017 was performed. Results : A total of 43 cases of involutional entropion repair were preformed in this time period. Fourteen eyelids of 12 patients had the combined procedure. There were no failures with a median follow-up of 29 months. Mean operative time, recorded in 10 patients, was 15 ± 2.2 minutes. Complications were minimal. Conclusions : The combination of the modified Bick quick strip procedure and Quickert sutures requires minimal surgical dissection and provides excellent results for the treatment of involutional entropion.